PENGARUH UKURAN PERUSAHAAN, OPINI AUDITOR DAN PROFITABILITAS TERHADAP AUDIT DELAY - Ni Luh Ade Dwi Anggreni; Sang Ayu Putu Arie Indraswarawati; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2022)
Audit Delay is the length of time from the closing date of the company's financial year to the date of issuance of the auditor's report. This study aims to examine how the influence of company size, auditor opinion and profitability on Audit Delay in companies listed on the Indonesia Stock Exchange in 2017 - 2019. The population of this study is the mining sector companies listed on the Indonesia Stock Exchange in 2017 - 2019 as many as 67 company. This is a quantitative study, and the samples were collected using the purposive sampling approach, yielding 99 samples from 33 firms. This research uses logistic regression analysis method. From the analysis test results, it was found that company size and auditor's opinion had no significant effect on Audit Delay, while profitability had a negative and significant effect on Audit Delay.